Dayah Education Curriculum Transformation: Building Targeted and Inclusive Education in the Modern Era - Alfi Khaira; Syamsuddin Syamsuddin; Nursanjaya Nursanjaya; Mauludi Mauludi (LPPM Universitas Malikussaleh, 2023)
Curriculum and learning in pesantren have a close relationship and support each other in creating holistic Islamic education. The curriculum acts as a teaching and learning design and arrangement that includes long-term, medium, and short-term goals in accordance with the periodisation of learner development. These goals must be in accordance with human nature and lead to the realisation of Muslim personality character. Learning in pesantren is the implementation of the curriculum, not only conveying learning materials, but changing student behaviour through direct experience. The learning process organises the environment so that the teaching and learning process occurs properly and creates conditions that allow students to learn materials in accordance with educational objectives. In addition, learning in pesantren also focuses on developing the character of students in accordance with Islamic values, beyond mere academic learning. Thus, curriculum and learning in pesantren have a crucial role in creating a holistic education, covering intellectual, moral, and spiritual aspects, and in accordance with Islamic values..